Роль еволюції в інвазіях судинних рослин - Бурда, Р.І. (Фактори експериментальної еволюції організмів, 2015)
Aims. Identify possible evolutionary changes that promote invasion of vascular plants. Methods. This is a critical analysis of scientifi c publications on evolutionary changes of vascular plants in the invasion of alien species in terms of secondary area. This is a fi xed evolutionary change as alien species, and so native species. Conclusions. The following a brief review of evolutionary changes that promote invasion of vascular plants. The adaptive phenotypic differentiation and genetic polymorphism of local populations of native species in secondary area are accentuated. Displaying role of spontaneous hybridization processes in cases of successful migration of vascular plants. Highlight threat coming biotic homogenization on different levels of biota. Keywords: alien species, biotic homogenization, evolution, invasion, hybridization, vascular plants.